Expression of HIF-1α in cycling stretch-induced osteogenic differentiation of bone mesenchymal stem cells - Yu, Haibo (Mol Med Rep, 2019)
During orthodontic treatment, mechanical force is applied to the teeth, and following a series of complex metabolism changes, the position of the teeth in the alveolar bone change. This process is closely associated with primitive bone mesenchymal stem cells (BMSCs), which may differentiate into osteoblasts precursor cell. A hypoxic microenvironment may be caused by orthodontic mechanical forces between the alveolar bone and the root. Hypoxia-inducible factor 1α (HIF-1α) is a specific receptor that adapts to a hypoxic environment. The present study was designed to investigate whether HIF-1α was involved in the osteoblastic differentiation of BMSCs induced by cyclic tensile stress. During this process, HIF-1α mRNA and protein expression were detected using a reverse transcription-quantitative polymerase chain reaction and western blotting. It was revealed that alkaline phosphatase activity increased in a time-dependent manner in three different stretching strength groups, which indicates that cyclic stretch promotes the osteogenic differentiation of BMSCs. The optimal force stage of osteogenesis was an unexpected discovery, which will provide theoretical guidance for selecting the most suitable orthodontic force for tooth movement in clinical orthodontic treatment. Most importantly, all experiments revealed that HIF-1α mRNA and protein were significantly increased following stretching treatment in BMSCs. It was therefore concluded that HIF-1α may be involved in BMSCs modulating osteogenic metabolism during exposure to cyclic stretch and a hypoxic microenvironment, which may prove useful for the reconstruction of a jaw during orthodontic treatment.